Echoes of ‘Nemi’? Patterns of Challenge, Sexual Violence and Substitution in Sir Orfeo and Sir Degaré - Sharon Rowley (Etudes Epistémè)
This essay examines patterns involving challenge, single combat, substitutions, paternity, sovereignty, tree symbolism and raptus in the Middle English Breton lays Sir Orfeo and Sir Degaré through the lens of Frazer’s The Golden Bough, and specifically his account of the cult of Diana Nemorensis. Re-examining these much-studied motifs in the context of the ‘rite of Nemi’, this paper sheds new light on some lingering puzzles such as the ympe-tre, Heurodis’ name and abduction, along with the king’s exile and restoration in Sir Orfeo, and the forest grove(s), challenges, violence and substitutions in Sir Degaré. In these poems, elements of the paradigm repeat and vary in compelling ways, suggesting that this symbolic web of literary and narrative elements was symbolically meaningful and structurally effective for Middle English poets exploring themes of identity, sovereignty, sexuality, and death.